Emotion perception, but not affect perception, is impaired with semantic memory loss - Lindquist, Kristen A. (2014)
For decades, psychologists and neuroscientists have hypothesized that the ability to perceive emotions on others’ faces is inborn, pre-linguistic, and universal. Concept knowledge about emotion has been assumed to be epiphenomenal to emotion perception. In this paper, we report findings from three patients with semantic dementia that cannot be explained by this “basic emotion” view. These patients, who have substantial deficits in semantic processing abilities, spontaneously perceived pleasant and unpleasant expressions on faces, but not discrete emotions such as anger, disgust, fear, or sadness, even in a task that did not require the use of emotion words. Our findings support the hypothesis that discrete emotion concept knowledge helps transform perceptions of affect (positively or negatively valenced facial expressions) into perceptions of discrete emotions such as anger, disgust, fear and sadness. These findings have important consequences for understanding the processes supporting emotion perception.